(untitled) (Journal of Fiber Bioengineering and Informatics, 2012)
This research carries out non-touched anthropometric measurements on 200 male university students aged from 19-26. 10 measurements relevant to the body neck were drawn in considering the necessary measurements in the pattern design of the fashion collar, This research utilizes the SPSS software to carry out a frequency distribution analysis and cluster analysis for the sample. 5 characteristic indices were elected in a statistical approach. These characteristic indices provide more reference measurements to the structural design of the men's fashion collar, it can be used to serve as the establishment of specification series for men's wear and for ready-to-wear production.